On the longitudinal motion of a thin ship travelling with constant forward speed in deep sea - Dat, Nguyen Tien (Vietnam Journal of Mechanics, 1993)
In this paper, the problem of the longitudinal motion of a thin ship with a constant forward speed and direction parallel to wave direction is solved by using Fourier transform and expanding the velocity potential in Fourier integral on Eigen functions. The influence of the forward speed on the velocity potential of fluid is considered. In the case of a thin ship with zero - forward speed the result shown good agreement with the one obtained by other authors.